2009
DOI: 10.3892/mmr_00000196
|View full text |Cite|
|
Sign up to set email alerts
|

HER 2/neu protein expression in gastric cancer is associated with poor survival

Abstract: Abstract. The presence of Her 2/neu has been reported in gastric cancer, but its impact on patient survival remains unclear. The purpose of this study was to investigate the expression of Her 2/neu in gastric cancer. a total of 218 paired resected gastric cancer and corresponding normal specimens were collected. Her 2/neu protein expression was assessed by immunohistochemical staining. The correlation between Her 2/neu expression and patient clinicopathological parameters was evaluated and the prognostic signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Identification of biological markers ability to predict risk of prognosis in breast cancer is limited. To improve the clinical outcome of patients with advanced breast carcinoma, it is necessary to target novel biomarker genes, which appear to be involved in carcinoma development, as we had described previously [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Identification of biological markers ability to predict risk of prognosis in breast cancer is limited. To improve the clinical outcome of patients with advanced breast carcinoma, it is necessary to target novel biomarker genes, which appear to be involved in carcinoma development, as we had described previously [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…In gastric cancer (GC), HER2 gene amplification would result in tumors having both greater invasive and proliferative capacity [4], and several authors have suggested that HER2 may involve poor outcome in patients with gastric cancer [5][6][7]. Although an increase in the HER2 gene copy-number has been demonstrated in 10% to 30% GC patients, different authors and meta-analysis differ in terms of the actual number of patients overexpressing the protein [7][8][9][10]. Most of these discordances can be explained by the subjectivity of the techniques used to assess HER2 gene amplification and overexpression (ISH and IHC), scoring criteria [11], tumor heterogeneity and tissue sampling errors [12].…”
Section: Introductionmentioning
confidence: 99%